Kaons in a hot and flavor-asymmetric medium - Ruivo, M. C. (1999)
We investigate the behavior of kaons in a flavor-asymmetric quark medium at finite temperature, within SU(3) Nambu-Jona-Lasinio type models. The effect of the Fermi sea on kaon properties is weaker in the model which includes a vector-pseudovector interaction than in the model without it. The study of the combined effect of density and temperature on the vacuum and kaon properties shows that the low temperature regime does not change significantly the effects observed at T = 0; as the temperature increases the mass splitting between K+ and K- modes, however reduced, is still meaningful.